Knowledge, awareness and practices towards exclusive breastfeeding among lactating mothers in Kashmir, North India: a hospital based cross sectional study - Nabi, Sahila; Zahoor, Nazia; Muzamil, Furqanah (International Journal Of Community Medicine And Public Health, 2023)
Background: Addressing good breastfeeding practices in lactating mothers is important as it helps in bringing about a positive change in the behaviour, attitude, and practice with appropriate health education. Hence, this study was conducted to determine the knowledge, awareness and practices of lactating mothers regarding breastfeeding and identify the factors associated with it. Methods: We conducted this hospital based cross sectional study among 349 lactating mothers at pediatric outpatient department of a tertiary care centre in Kashmir, North India between July to October 2022. Details regarding the socio-demographic characteristics and awareness/knowledge about the breastfeeding were collected using pretested semi-structured questionnaire. Data was collected through face-to-face interview. Results: Majority of the participants 305 (87.4%) knew the meaning of exclusive breastfeeding and it is important for both mother and child. About (68.8%) had moderate knowledge about breastfeeding. Chi square test showed a significant association between level of knowledge and age, education and family type where p value was 0.000. Conclusions: Our findings showed that the practice towards exclusive breast-feeding was low. Thus, it is important to provide prenatal education to mothers and fathers on breast-feeding. We also recommend strengthening the public health education campaigns to promote breast-feeding.